Generation Y-Turnover: A Complementary Fit Perspective - Queiri, Abdelbaset; Madbouly, Araby (Journal of Economics and Behavioral Studies, 2017)
Generation Y becomes the main pillar of workforce around the world. This generation enters the workplace with different values and characteristics from their counterparts of other generational workforces. In Malaysia, generation Y employees are well known of their high job mobility. Human resource managers are in dilemma of how to retain this new workforce? This paper serves the purpose to respond to such queries by investigating the factors contributing to Generation Y employees’ Turnover from a complementary fit perspective. This study was conducted in Malaysian Business Process Outsourcing Sector (PBO). The total sample was comprised of 318 respondents belong to generation Y employees. The data was analysed in Amos using two steps approach. Extrinsic, freedom and demand abilities fit were the predictors of Generation Y employees’ intention to quit in Malaysian BPO sector.Using cross sectional method limits our understanding to whether the predictors of turnover intention were due to career effects or generational effects. This study provides empirical evidences to Malaysian HR Managers to what makes generation Y employees leave the organization. This is a better surrogate of the existed anecdotal information. Furthermore, this study informs HR Managers that stereotyping the findings from Western context may be treated with caution.